Peran Citra Merek dalam Memediasi E-Wom terhadap Minat Beli Produk Handphone di Sosial Media Facebook - Azis, Fachri; Savitri, Citra; Pramudita Faddila, Syifa (Journal of Management and Bussines (JOMB), 2024)
This research aims to investigate the influence of electronic Word of Mouth (e-Wom) on consumer purchase intention, with brand image as a mediating variable. e-Wom is increasingly crucial in digital marketing, shaping perceptions and purchasing decisions. Brand image is expected to explain the relationship between e-WOM and consumer buying interest. Quantitative methods as the main basis. The type of research used in this research is descriptive and verification. The results of this research found that e-Wom influences the Buying Interest variable through the mediation of Brand Image, there is a positive and significant indirect relationship. It is hoped that the practical implications of these findings can guide marketing practitioners in designing more effective strategies for managing e-WOM and building a strong brand image to increase consumer purchasing interest in the digital marketing environment. Keyword : Brand Image, E-Wom, Facebook, Purchase Intention